Exploring Positional Knowledge: Using Theory To Teach Bias - Weeks, Thomas; Johnson, Melissa (Communications in information literacy, 2025)
In this article, the authors explain how librarians can use positionality theory to understand how students produce value judgments around questions of bias, authority, and credibility. Librarians can help guide students to recognize the student’s own positionality when approaching issues of bias. Students are often instructed to choose credible sources for their research, which they often interpret as sources that avoid bias. Source evaluation tools and checklists, such as the CRAAP test and SIFT, also tell students to watch out for biased language. Unfortunately, many people, students and librarians alike, misunderstand bias and fail to recognize its significance in the information search process. Positionality theory, which locates individuals within their social context, offers librarians a way to conceptualize bias’s function in information literacy as a social construct in order to teach students about the complexity of bias.